Development of a scale assessing retired older adults' attitudes to volunteering. (30th March 2021) - Dana, Liyuwork Mitiku; Jongenelis, Michelle I.; Jackson, Ben; Newton, Robert U.; Pettigrew, Simone
Abstract: Objective: Given positive attitudes to volunteering are likely to be associated with support for volunteering and individual participation, this study aimed to develop and test a 10‐item 'attitudes to formal volunteering' scale for retired older adults that could be used to inform intervention efforts. Method: A sample of 801 Australian retirees (62% female; mean age: 71.9 years) completed a survey that included the attitude scale, demographic items and questions assessing engagement in volunteering. Results: A principal component analysis identified two factors (general attitude to volunteering and attitude to participating in volunteering) that together accounted for 64% of the variance in attitude scores. A confirmatory factor analysis indicated the two‐factor model was an excellent fit to the data. Cronbach's alphas for both factors were >0.80, and both were positively associated with volunteering engagement. Conclusion: The proposed scale is a potentially useful instrument for measuring attitudes to volunteering among retired older adults.